Core, periphery and (neo)imperialist international relations (2013)
This article analyzes the core–periphery dynamics that characterize the International Relations discipline. To this end, it explores general insights offered by both science studies and the social sciences in terms of the intellectual division of labor that characterizes knowledge-building throughout the world, and the social mechanisms that reproduce power differentials within given fields of study. These arguments are then applied to International Relations, where specific factors that explain the global South’s role as a periphery to the discipline’s (mainly US) core and the ways in which peripheral communities place themselves vis-à-vis International Relations’ (neo)imperialist structure are both explored.